2011
DOI: 10.1093/nar/gkr1040
|View full text |Cite
|
Sign up to set email alerts
|

mTOR signaling regulates the processing of pre-rRNA in human cells

Abstract: Signaling through the mammalian target of rapamycin, complex 1 (mTORC1), positively regulates the transcription of ribosomal RNA (rRNA) and the synthesis of ribosomal proteins, thereby promoting the complex process of ribosome biogenesis. The major rRNAs are transcribed as a single precursor, which must be processed to create the 5.8S, 18S and 28S rRNAs. We used a new non-radioactive labeling approach to study the effects of rapamycin, an inhibitor of mTORC1, on rRNA synthesis. Rapamycin not only impaired synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 35 publications
2
81
0
Order By: Relevance
“…U6), whose promoters typically do not possess B-box elements and utilize a separate complement of transcription factors (34). It is known that mTOR regulates all three classes of RNA polymerases to facilitate ribosome biogenesis (6) and that, similar to SIRT7, it can localize to nucleoli (31). Therefore, we propose that SIRT7 functions in ribosome biogenesis and protein synthesis are partly mediated by its association with mTOR (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…U6), whose promoters typically do not possess B-box elements and utilize a separate complement of transcription factors (34). It is known that mTOR regulates all three classes of RNA polymerases to facilitate ribosome biogenesis (6) and that, similar to SIRT7, it can localize to nucleoli (31). Therefore, we propose that SIRT7 functions in ribosome biogenesis and protein synthesis are partly mediated by its association with mTOR (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…2E). It has been reported that perturbations in rRNA processing steps can lead to the accumulation of prerRNA intermediates (30,31), which could result in longer half-lives of the pre-rRNA intermediates like 5Ј external transcribed spacer near 18S and internal transcribed spacer. However, we found that the steady state levels of rRNA measured by qPCR are decreased after SIRT7 knockdown (supplemental Fig.…”
Section: Sirt7 Has An Rna-independent Nucleolar Localization and Intementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the mTOR pathway controls rRNA transcription and production of ribosomal proteins in response to nutrient, growth factors, and serum (19)(20)(21).…”
mentioning
confidence: 99%
“…mTORC1 positively regulates many anabolic processes, with the role of mTORC1 signaling in translational initiation being the best understood. More recently a function of mTOR signaling in ribosome biogenesis has also been proposed (8)(9)(10)(11)(12). In particular, mTOR has been implicated in the control of RNA polymerase I transcription and rRNA processing.…”
mentioning
confidence: 99%